PROTECTION OF THE RIGHTS OF PERSONS WITH DISABILITIES TO WORK: KAZAKHSTAN’S EXPERIENCE FROM THE PERSPECTIVE OF INTERNATIONAL LAW AND EU LAW - Adibayev, Asset; Susi, Mart (Pravni zapisi, 2023)
In spite of the ratification of Convention on the Rights of Persons with Disabilities, by the majority of States, this human category still faces various challenges. The gap between the declarative nature of the equal rights of the persons with disabilities and the practical implementation of the concept of equality is especially evident in the field of access to employment. Although the majority of countries, including Kazakhstan, have transposed the ideas of equal treatment of the persons with disabilities into national legislation, the situation remains unsatisfactory, and one can ask: why? This is especially relevant in labor area and connected to the insufficient governmental supervision of how legal principles are enforced by private actors in the workplace. Specific national effective enforcement mechanisms and remedies are needed, hand-in-hand with international supervision, to minimize the discrepancy between what the countries have committed to and how they comply with the obligations to safeguard the rights of the persons with disabilities. Kazakhstan needs to complement its commitment to these rights with a national action plan.
Keywords: right to work of the persons with disabilities; inclusive education; law as practice; declarative nature of human rights law; international conventions; local legislation